Il Servizio alla Verità nel Processo Matrimoniale - Bianchi, Paolo (Ius canonicum, 2017)
Truthin the canonical marriage process avails of different meanings: factual truth, the real course of the marriage events presented for judicial examination; the doctrinal truth to be respected in the decision; truth with a legal dimension, i.e. which contextualizes the marriage in terms of the canonical discipline; and finally, as truth oriented towards spiritual salvation. The pursuit of truth is a recurring theme papal addresses to the Roman Rota from Pius XII to Francis and it is set out again in the Mitis Iudex Dominius Iesus: pursuit and service to the truth are key features of the latest revision of the regulation. Some institutions set out to guide this process towards truth: the appropriate understanding of contradictory positions; the primacy of favor veritatis in relation to both favor personae and favor matrimonii; the fundamental importance of moral certainty in the canonical process system; the recognition of the proof-value of the statements made by the parties involved, deferred to in a prudent and balanced way.